Объяснение:
1)Zn+ H2SO4 = ZnSO4 + H2↑
ZnSO4 + BaCl2 = BaSO4↓ + ZnCl2
ZnCl2 + 2NaOH = Zn(OH)2↓ + 2NaCl
Zn(OH)2 = ZnO + H2O
ZnO + H2 = Zn + H2O
2) Si + O2 = SiO2
SiO2 + 2KOH = K2SiO3 + H2O
K2SiO3 + CaCl2 = CaSiO3↓ + 2KCl
CaSiO3 = CaO + SiO2
SiO2 = Si + O2
Объяснение:
1)Zn+ H2SO4 = ZnSO4 + H2↑
ZnSO4 + BaCl2 = BaSO4↓ + ZnCl2
ZnCl2 + 2NaOH = Zn(OH)2↓ + 2NaCl
Zn(OH)2 = ZnO + H2O
ZnO + H2 = Zn + H2O
2) Si + O2 = SiO2
SiO2 + 2KOH = K2SiO3 + H2O
K2SiO3 + CaCl2 = CaSiO3↓ + 2KCl
CaSiO3 = CaO + SiO2
SiO2 = Si + O2